Irma Taavitsainen y Päivi Pahta (eds.), Medical and Scientific Writing in Late Medieval English, Cambridge: Cambridge University Press, 2004. - Mariana Hidalgo Martínez; Paola Jiménez Álvarez (Medievalia, 2016)
Irma Taavitsainen y Päivi Pahta (eds.), Medical and Scientific Writing in Late Medieval English, Cambridge: Cambridge University Press, 2004.